1: SUBDUCTION, SLAB DETACHMENT AND MINERALIZATION: THE NEOGENE IN THE APUSENI MOUNTAINS AND CARPATHIANS - Neubauer F.; Lips A.; Kouzmanov K.; Ivǎşcanu P.; Lexa J. (My University, 2005)
The Inner Carpathians comprise several distinct Neogene late-stage orogenic Pb-Zn-Cu-Ag-Au ore districts. The mineral deposits in these districts are closely related to volcanic and subvolcanic rocks, and represent mainly porphyry and epithermal vein deposits, which formed within short periods of time in each district. Here, we discuss possible geodynamic and structural controls that suggest why some of the Neogene volcanic districts within the Carpathians comprise abundant mineralization, while others are barren. The Neogene period has been characterized by an overall geodynamic regime of subduction, where primary roll-back of the subducted slab and secondary phenomena, like slab break-off and the development of slab windows, could have contributed to the evolution, location and type of volcanic activity. Structural features developing in the overlying lithosphere and visible in the Carpathian crust, such as transtensional wrench corridors, block rotation and relay structures due to extrusion tectonics, have probably acted in focusing hydrothermal activity. As a result of particular events in the geodynamic evolution and the development of specific structural features, mineralization formed during fluid channelling within transtensional wrench settings and during periods of extension related to block rotation. In the Slovakian ore district of the Western Carpathians, Neogene volcanism and associated mineralization were localized by sinistral, NE-trending wrench corridors, which formed part of the extruding Alcapa block. The Baia Mare ore district, in the Eastern Carpathians, reflects a transtensional wrench setting on distributed oversteps close to the termination of the Dragos Voda fault. There, mineralization was spatially controlled by the transtensional Dragos Voda master fault and associated cross-fault systems. The Golden Quadrangle Cu-Au ore district of the Southern Apuseni Mountains reflects an unusual rotated transtensional/extensional setting close to the termination of a graben system. There, fluid flow was probably localized by fault propagation at the inner tip of the graben system. The spatial and temporal evolution of the magmatism and its changing geochemical signature from (N)W to (S)E strongly suggests a link with the contemporaneous northeastward roll-back of the subducted slab and a progressive southeastward detachment during accelerating roll-back. This geodynamic evolution is further supported by the present-day overall and detailed mantle lithospheric density images, the present-day heat flow patterns, the crustal architecture and its interpreted evolution, and the spatial and temporal evolution of depocentres around the Carpathian arc. In contrast to all these features, the mineral deposits in the West Carpathians, East Carpathians and Apuseni Mountains are too synchronous with respect to their individual volcanic history and contrast too much with younger volcanics of similar style, but barren, in southeastern parts of the Carpathians to simply link them directly to the slab evolution. In all three districts, the presence of magmatic fluids released from shallow plutons and their mixing with meteoric water were critical for mineralization, requiring transtensional or extensional local regimes at the time of mineralization, possibly following initial compressional regimes. These three systems show that mineralization was probably controlled by the superposition of favourable mantle lithospheric conditions and partly independent, evolving upper crustal deformation conditions. In the 13 to 11 Ma period the dominant mineralization formed all across the Carpathians, and was superimposed on structurally favourable crustal areas with, at that time, volcanic-hydrothermal activity. The period may reflect the moment when the (upper part of the) crust failed under lithospheric extension imposed by the slab evolution. This crustal failure would have fragmented the overriding plate, possibly breaking up the thermal lid, to provoke intensive fluid flow in specific areas, and allowed subsequent accelerated tectonic development, block rotation and extrusion of a "family of sub-blocks" that are arbitrarily regarded as the Tisia-Dacia or Alcapa blocks, even though they have lost their internal entity. © 2005 Elsevier B.V. All rights reserved.
Keywords: EPITHERMAL SYSTEM; HYDROTHERMAL SYSTEM; OVERSTEP; PORPHYRY SYSTEM; RELAY STRUCTURE; SLAB BREAK-OFF; SUBDUCTION; WRENCH CORRIDOR; Neogene; Cenozoic::Neogene